1998
DOI: 10.1073/pnas.95.25.14769
|View full text |Cite
|
Sign up to set email alerts
|

SMAD3/4-dependent transcriptional activation of the human type VII collagen gene ( COL 7A1 ) promoter by transforming growth factor β

Abstract: The human type VII collagen gene (COL7A1) recently has been identified as an immediate-early response gene for transforming growth factor ␤ (TGF-␤)͞SMAD signaling pathway. In this study, by using MDA-MB-468 SMAD4؊͞؊ breast carcinoma cells, we demonstrate that expression of SMAD4 is an absolute requirement for SMADmediated promoter activity. We also demonstrate that the SMAD binding sequence (SBS) representing the TGF-␤ response element in the region ؊496͞؊444 of the COL7A1 promoter functions as an enhancer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
128
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 38 publications
12
128
0
Order By: Relevance
“…Aside from the reduction of lung fibrosis, we found that loss of Smad3 inhibited bleomycin-induced collagen accumulation in the lung interstitium. Recent evidences have shown that Smad3 is involved in the transcriptional activation of TGF-␤-mediated stimulation of collagen expression (5,32,33). Smad3 is necessary for the formation of transcriptional activation complex in the stimulation of type I collagen gene expression by TGF-␤ ligands in human skin fibroblasts (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the reduction of lung fibrosis, we found that loss of Smad3 inhibited bleomycin-induced collagen accumulation in the lung interstitium. Recent evidences have shown that Smad3 is involved in the transcriptional activation of TGF-␤-mediated stimulation of collagen expression (5,32,33). Smad3 is necessary for the formation of transcriptional activation complex in the stimulation of type I collagen gene expression by TGF-␤ ligands in human skin fibroblasts (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Multimers of SBE when placed in front of a minimal promoter reporter construct provide a strong enhancer function for TGF-b family members. SBE-like sequences have been shown to be critically important for TGF-binducibility of multiple TGF-b responsive genes (Dennler et al, 1998;Vindevoghel et al, 1998;Hanai et al, 1999;Nagarajan et al, 1999;Brodin et al, 2000;Chen et al, 2000;Taylor and Khachigian, 2000). The crystal structure of Smad3 MH1 domain with SBE showed that the b-hairpin loop in Smad3 is in contact region with the SBE (Shi et al, 1998).…”
Section: Transcriptional Control By Smadsmentioning
confidence: 99%
“…Smad2 is unable to bind directly to DNA because it contains an extra exon just N-terminal of the b-hairpin loop (Dennler et al, 1998;Yagi et al, 1999). SBE-like sequences have been identi®ed in the promoters of multiple TGF-b responsive genes, including plasminogen activator inhibitor-1 (PAI-1) (Dennler et al, 1998;Luo et al, 1999), junB (Jonk et al, 1998), type VII collagen (Vindevoghel et al, 1998) and the germline immunoglobulin Ia region (Hanai et al, 1999;Pardali et al, 2000a;Zhang and Derynck, 2000). Mutation of SBEs attenuate TGF-b inducibility.…”
Section: Introductionmentioning
confidence: 99%